Polymorphisms in NLRP1 Gene Are Associated with Type 1 Diabetes - Xiaoxiao Sun; Ying Xia; Yue Liu; Yanfei Wang; Shuoming Luo; Jian Lin; Gan Huang; Xia Li; Zhiguo Xie; Zhiguang Zhou (Journal of Diabetes Research)
Objective. The aim of this study was to clarify the association of two single-nucleotide polymorphisms (SNPs) (rs11651270 and rs2670660) in the NLRP1 (NLR family pyrin domain containing 1) gene with type 1 diabetes (T1D) in the Chinese Han population. We hypothesize that mutations in the NLRP1 gene may affect the susceptibility to T1D. Materials and Methods. A case control study was designed, and participants fulfilling the diagnostic criteria of classical T1D as well as nondiabetic controls were enrolled in the study. The polymorphisms rs11651270 and rs2670660 were genotyped by polymerase chain reaction (PCR) and Sanger sequencing. Chi-squared test and logistic regression analysis were performed to compare the distributions of the allele and genotype between cases and controls. Kruskal-Wallis one-way ANOVA was used to compare the characteristics of different genotypes in participants with T1D. Results. A total of 510 participants with classical T1D as well as 531 nondiabetic controls were enrolled in the study. The two groups were matched in sex (p=0.418). The age (p<0.001) and BMI (p<0.001) were significantly lower in cases compared to controls. Significantly higher values were observed for fasting plasma glucose (FPG) (p<0.001) and 2 h postprandial plasma glucose (PPG) (p<0.001) in individuals with T1D. Regarding the allelic model, the minor allele C of rs11651270 was significantly associated with lower risk of T1D compared with the T allele (OR=0.714, 95% CI=0.579-0.882). Both rs11651270 and rs2670660 polymorphisms were associated with T1D in the Chinese Han population under a dominant model (OR=0.648, 95% CI=0.503-0.834 and OR=0.716, 95% CI=0.549-0.934, respectively) and an overdominant model (OR=0.663, 95% CI=0.511-0.860 and OR=0.711, 95% CI=0.541-0.935, respectively). Additionally, the polymorphism rs11651270 was also related to T1D in an additive model (OR=0.719, 95% CI=0.583-0.887). Most importantly, when we analyzed the clinical characteristics of T1D individuals with different genotypes, we found that the age of onset with the TT genotype at rs11651270 was younger than those with the other two genotypes (p=0.001). Conclusions. SNPs in the NLRP1 gene were associated with T1D, as well as the age of onset in the Chinese Han T1D individuals. Our study indicated that the NLRP1 gene might play a pivotal role in the etiopathogenesis of T1D and could be applied to genetic screening of T1D in the Chinese Han population.